El Archivo del Reino de Valencia y la información geográfica en sus fondos - Torres Faus , Francesc (Tábula, 2024)
Los fondos del Archivo del Reino de Valencia conservan algunas agrupaciones documentales que son una fuente de información geográfica importante. Entre estos fondos podemos distinguir aquellos referentes a las instituciones del Antiguo Régimen, tanto los forales como los borbónicos, y los fondos contemporáneos procedentes de la Administración Periférica del Estado. Entre los primeros destaca el fondo de la Bailía, el del Maestre Racional, la Real Audiencia Foral y borbónica, los “procesos de Madrid” del Consejo de Aragón, la documentación de la Orden de Montesa, la documentación de las Comunidades de Regantes y la colección cartográfica. Los fondos contemporáneos aportan la información más reciente, y entre ellos destaca el fondo de la Delegación Provincial del Ministerio de Hacienda, el fondo de la Gerencia del Catastro y el de la Organización Sindical Española. The archives of the Archive of the Kingdom of Valencia preserve some documentary series that are an important source of geographic information. Among these collections we can distinguish those referring to the institutions of the Ancient Regime, both the foral and the bourbon, and the contemporary collections from the Peripheral Administration of the State. Among the former are the Bailia collection, the Rational Master’s collection, the Foral and Bourbon Royal Audience, the “Madrid processes” of the Council of Aragon, the documentation of the Order of Montesa, the documentation of the Irrigation Communities and the cartographic collection. The contemporary collections provide the most recent information, and among them are the collection of the Provincial Delegation of the Ministry of Finance, the collection of the Cadastre Management, and the collection of the Spanish Trade Union Organization.